IMPLEMENTASI ALGORITMA BEST-FIRST SEARCH PADA APLIKASI PENJUALAN LAPTOP BEKAS BERBASIS MOBILE - Qadr Buana Mahjoenis (Jurnal Riset Multidisiplin Edukasi, 2025)
The development of mobile-based e-commerce in Indonesia has grown rapidly, especially with the demand for systems that accommodate the bargaining culture still prevalent in society. This study aims to develop a mobile-based used laptop sales application with a bargaining system, optimized using the Best-First Search (BFS) algorithm. The implementation of this BFS algorithm allows the application to provide product recommendations for used laptops based on criteria entered by users, such as category, price, RAM, and storage capacity. The study also integrates a bargaining system to enhance interaction between buyers and sellers, with validation carried out by the admin. The results show that the application of BFS in mobile apps can improve product search relevance and ease, as well as interactivity in transactions. This application is expected to contribute to the development of e-commerce in Indonesia by combining modern technology and the bargaining culture.